Empowering the society through companies CSR agenda - Sulaiman, Noor Adwa; Muhamad, Rusnah (2017)
Topic of socioeconomic issue is one of the most widely discussed globally as it gives effects to occupation, education, income, wealth, and place of residence of individuals.These social challenges should be addressed and resolved because to enhance individuals’ contribution to economic and social life of their society and reduce social tensions and conflicts that negatively affects country’s economic development. For this reason, in the Eleventh Malaysia Plan (2016-2020), the Malaysian Government stresses on the importance of participation of companies in empowering society to improve socioeconomic that could support equitable society.The empowerment programs aim to improve the education, quality of life and wellbeing of individuals and groups in society through reducing wealth gap, racial imbalance and promoting employment equity. One way to initiate greater involvement of the companies in socioeconomic development of the society is through CSR agenda.Specifically, the CSR agenda through empowerment activities (such as trainings programs, educational sponsorship mentorship program and learning and development programs) is believed to have a positive implication on society by way of improving wealth, education and skills of the individuals.Hence, this paper aims to develop measurement of empowerment in companies CSR agenda.